Imaging phosphorylated peptide distribution in human lens by MALDI MS1. Issue 12 (21st June 2015) - Jiao, Jing; Miao, Aizhu; Zhang, Ying; Fan, Qi; Lu, Yi; Lu, Haojie
<x xml:space="preserve">Abstract</x> A new strategy for on-tissue dephosphorylation treatment was established for phosphorylated peptide distribution by mass spectrometry imaging.